Rock? Plant? Animal? : how nature keeps us guessing - Kaner, Etta (Owlkids Books, 2022)
"Pretty Tricky meets Do Frogs Drink Hot Chocolate in this guessing-game book that explores how in nature, things aren't always what they seem ... ... sometimes what looks like a plant is actually a rock or what looks like a rock is actually an animal or what looks like an animal is actually a plant. In ROCK? PLANT? ANIMAL?, young readers are invited to guess what they are looking at as they are introduced to animals that don't look like animals, plants that don't look like plants, and rocks that don't look like rocks! The recto of each spread has a large spot illustration of either a rock, plant, or animal, prompting the reader to make their best guess. There will be surprises but the idea is not to trick readers - anyone who knows children knows that sometimes they want to be right! - so much as invite them to really consider what they are looking at, using what they know already, as well as what they have learned from the basic definitions of a rock, plant, or animal provided in the book's intro. And Brittany's inviting, beautifully realistic illustrations are up for the scrutiny! A page turn reveals the answer by showing the featured plant/rock/animal situated within a detailed scene, as well as a brief description of the rock/plant/animal, including why it looks the way it does. Fourteen "species" are presented. Includes a glossary."--